2c + 4 - 3c = -9 + c + 5 -c + 4 = c - 4 -2c = -8 2c = 8 c = 4
2c-10
c + c + 2c + c + c = 6c
3c
The expression is 5d+2c and the unknown variables are d and c
2c + 4 - 3c = -9 + c + 5 -c + 4 = c - 4 -2c = -8 2c = 8 c = 4
4 + 3c = 2c + 2Subtract 4 from each side:3c = 2c - 2Subtract 2c from each side:c = -2
The like terms are sums of b terms and c terms separately 5c+2c+3c+4b 5c +2c + 4b + 3c => 10c + 4b
4a + 3c - 2b - c + a - b = 5a - 3b + 2c
c-2b
-2c
-((3c - 4)(3c + 4)(2c - 5)(2c + 5))
It is:- 3c+5 = c+15 Subtact 5 and c from both sides: 2c = 10 Divide both sides by 2 to find the value of c: c = 5
a + 7b + 2c
ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.
2c+4c-3c+5c = 6c +2c = 8c
That's going to depend on the values of 'a', 'b', 'c', and 'f'.